The lady's chair and the ottoman - Tennyson, Noel. (New York : Lothrop, Lee & Shepard Books, 1987)
An ottoman has spent as long as he can remember trying to get close to a lady's chair; and though fortune separates them and they seem to come to unhappy ends, a marvelous coincidence reunites them in a very happy way.
Keywords: Furniture -- Fiction